REPRESENTATION OF POLITENESS STRATEGY BY MEMBERS OF COLLEGE STUDENT ORGANIZATION: A PRAGMATIC APPROACH - Dewi Rosaria Indah; Tri Achmad Efendi (Widya Mandala Surabaya Catholic University, 2025)
This study is aimed at figuring out politeness strategies used by college students’ organisation at STKIP Bina Insan Mandiri. As social human beings people need to maintain their relationships. One of the ways to carry it out is by demonstrating politeness. How the members of college students’ organisations at STKIP Bina Insan Mandiri performed this act was sought out. The politeness strategies for doing FTA’ is as its framework.This study used qualitative descriptive as its research design. It used two kinds validated questionnaires as its instruments to gather the needed data and as a means of triangluations. There were 40 sets of questionnaire got as the data and they were analysed and interpreted by making use of the politeness strategies by Brown & Levinson. Another set was distributed to the structural officers to confirms the findins. It was found out that most members of the students’ organisations were communicating in both channels: face to face and via chat apps. They performed negative politeness and positive politeness. It was verified by the structural officers that they understand how manage good communication hence had a good soft skill. They aware whom they were talking or speaking to and understand how to express their sentences well.